A Novel Candidate Molecule in the Pathological Grading of Gliomas: ELABELA - Artas, Gokhan; Ozturk, Sait; Kuloglu, Tuncay; Dagli, Adile Ferda; Gonen, Murat; Artas, Hakan; Erol, Fatih Serhat (Turkish Neurosurgical Soc, 2018)
AIM: To investigate the possible role of ELABELA (ELA) in the histopathological grading of gliomas. MATERIAL and METHODS: We retrospectively assessed pathological specimens of patients who underwent surgery for intracranial space-occupying lesions. Only primary glioma specimens were included in this study. We enrolled 11 patients histologically diagnosed with low-grade glioma and 22 patients with high-grade glioma. The ELA antibody was applied to 4-6-pm-thick sections obtained from paraffin blocks. Histoscores were calculated using the distribution and intensity of staining immunoreactivity. An independent sample t-test was used for two-point inter-group assessments, whereas one-way analysis of variance was used for the other assessments. p<0.05 was considered statistically significant. RESULTS: The histoscores of the control brain, low-grade glioma, and high-grade glioma tissues were found to be 0.08, 0.37, and 0.92, respectively. The difference in ELA immunoreactivity between the control brain tissue and glioma tissue was statistically significant (p<0.05). In addition, a statistically significant increase was observed in ELA immunoreactivity in high-grade glioma tissues compared with that in low-grade glioma tissues (p<0.05). CONCLUSION: ELA has an angiogenetic role in the progression of glial tumors. ELA, which is an endogenous ligand of the apelin receptor, activates the apelinergic system and causes the progression of glial tumors. Further studies with a large number of patients are necessary to investigate the angiogenetic role of ELA in glial tumors.
Keywords: Apelin; Apelin receptor; Astrocytoma; Elabela; Glioma